Efektivitas Solution Focused Brief Group Counseling Terhadap Tingkat Perilaku Adiksi Narkolema Siswa Kelas VIII SMP Negeri 9 Banjarbaru - Rahim, Rabin; Jarkawi, Jarkawi; Haryadi, Rudi (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2023)
Narcolemma addiction behavior is an addiction to pornography, it causes negative impacts on students such as concentration and focus in learning to be hampered, the process of interaction in the social environment is disrupted and the worst thing is to commit acts of harassment and immorality that violate the laws and norms of society. The purpose of this study was to see whether the solution focused brief group counseling (SFBGC) approach was effective in reducing narcolemma addiction behavior in class VIII D students of SMP Negeri 9 Banjarbaru and to determine the level of narcolemma addiction behavior before and after being given the intervention. This research used a quantitative method with a pre-experimental research design in the form of one group pre-test post-test. The sample is 30 subjects. The use of the instrument is adopted and modified from Sari's research (2019) which discusses the same variables, for the reliability of the questionnaire after validation of 0.905. Hypothesis testing using the Wilcoxon test. The conclusion obtained is that the SFBGC approach is effective in reducing the level of narcolemma addiction behavior.